Factors Affecting Stress Disorder in Airline X Pilots during the COVID-19 Pandemic - Titis Mariyamah; Johannes Hudyono; Anastasya Putri Liara (Jurnal MedScientiae, 2023)
Civil airline pilot is one of the jobs that often causes work stress. The COVID-19 pandemic that entered Indonesia in early 2020 saw a drastic decline in the aviation industry. This can affect airline pilots experiencing work stress. The purpose of the study was to determine whether there were any factors that influenced stress on airline X pilots during the COVID-19 pandemic. Sampling was taken using a non-probability sampling technique, the type of consecutive sampling. To obtain data from the results of the study using univariate analysis and bivariate analysis using the Chi-Square and Kolmogorov-Smirnov tests. This study uses a questionnaire instrument Depression Anxiety Stress Scales-21 (DASS-21). The results of the data were analyzed using the Chi Square and Kolmogorov-Smirnov test that there was a relationship between age (P=0.000), flight hours (P=0.002), and work duration (P=0.000) with work stress. There are 92 respondents who do not experience stress and as many as 5 respondents experience moderate stress.PThe COVID-19 epidemic with stress disorders in pilots did not have a big effect, male pilots experienced more work stress than women. Age, length of flight hours, length of work duration affect work stress.